1994
DOI: 10.1111/j.1528-1157.1994.tb02484.x
|View full text |Cite
|
Sign up to set email alerts
|

Vagus Nerve Stimulation for Treatment of Partial Seizures: 3. Long‐Term Follow‐Up on First 67 Patients Exiting a Controlled Study

Abstract: Vagus nerve stimulation (VNS) has demonstrated a significant anticonvulsant effect in preclinical studies, in pilot studies in humans, and in the acute phase of a multicenter, double-blinded, randomized study. After completion of a 14-week, blinded, randomized study, with 31 receiving high (therapeutic) VNS and 36 receiving low (less or noneffective) VNS, 67 patients elected to continue in an open extension phase. During the extension phase, all 67 patients received high VNS. Seizure frequency during the 3-mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
2
2

Year Published

1996
1996
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(95 citation statements)
references
References 10 publications
(12 reference statements)
2
89
2
2
Order By: Relevance
“…1,2,4,5,[8][9][10][11]15,[24][25][26][27][28] Five of the remaining studies used the mean or median frequency reduction from baseline. 3,14,17,22,23 The mean seizure reduction in these investigations was 42.8% (range 28%-66%). Four studies additionally included data on the percentage of patients achieving freedom from seizures, typically quoted at the 1-year time frame.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2,4,5,[8][9][10][11]15,[24][25][26][27][28] Five of the remaining studies used the mean or median frequency reduction from baseline. 3,14,17,22,23 The mean seizure reduction in these investigations was 42.8% (range 28%-66%). Four studies additionally included data on the percentage of patients achieving freedom from seizures, typically quoted at the 1-year time frame.…”
Section: Resultsmentioning
confidence: 99%
“…With extended follow-up durations from 1 to 6 years, the 7 publications identified here provide strong evidence for the use of VNS in multiple epilepsy syndromes over extended periods of treatment. With large, prospectively collected data sets, the investigations of George et al 14 and Salinsky et al 25 have served to confirm the utility of high-stimulation VNS for increased seizure control. BenMenachem et al 4 expanded the prospective application of VNS to patients with generalized seizures and LennoxGastaut syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due to the small number of patients and the fact that increased SWS is only one of several contributing factors to improved QOL together with decreased epileptiform activity, seizure frequency and severity. Parker et al 5 and George et al 30 reported that the effects of VNS are positively correlated to the length of the treatment period. In this view 9 months may still be a too short observation time to find effects on sleep architecture in addition to effects on epileptiform activity.…”
Section: Discussionmentioning
confidence: 99%
“…Beginning parameter settings of 30-Hz signal frequency, 500-s pulse width, 30 s on-time, and 5 minutes off-time have been found to be effective in double-blind, controlled studies, although these parameters may vary considerably in practice. 20,21 Incremental increases in output current of 0.25 to 0.5 mA every 2 to 4 weeks allow for gradual acclimation, and may ultimately increase a patient's tolerance for higher output current if required for optimal seizure control.…”
Section: Ncp System: Device and Surgical Proceduresmentioning
confidence: 99%